Disaster knowledge and awareness associated to preparedness in the First Congressional District in Zamboanga Del Norte - Campiseño, Joseph Salvel R. (2015)
Knowledge and awareness coming from the community on the natural and human-induced disasters are crucial for the preparedness activities to be responsive to the needs of the people. This study was conducted to ascertain the disaster knowledge, disaster awareness, and disaster preparedness in the local communities of the first congressional district in the province of Zamboanga del Norte to determine if disaster knowledge and awareness are associated to disaster preparedness among the constituents of the province. This study revealed that about 14 percent of the surveyed respondents possessed knowledge on disaster events, more than 75 percent were unaware about the presence of disasters, and almost 75cpercent were unprepared on disasters to take place. It was also found out that disaster knowledge and awareness were significantly associated to preparedness. Hence, educating the respondents provides better opportunities for them in enhancing local knowledge and community awareness to access information to the threats and impacts of all hazards, risks, and vulnerabilities and, consequently, develop preparedness scheme to prevent, mitigate, response, and manage the occurrence of disasters.
Keywords: Emergency management; Mindanao studies